Advanced Mesodermal (Müllerian) Adenosarcoma of the Ovary: Metastases to the Lungs, Mouth, and Brain - A. Daskalaki; S. Xenaki; E. Athanasakis; E. Chrysos; G. Chalkiadakis (Case Reports in Surgery)
Background. A malignant mixed Müllerian tumor (MMMT) is a malignant neoplasm found in the uterus, the ovaries, the fallopian tubes, and other parts of the body that contains both carcinomatous (epithelial tissue) and sarcomatous (connective tissue) components. Outcome of MMMTs is determined primarily by depth of invasion and stage. The metastatic background of these lesions is controversial and unknown. Case Report. A 75-year-old woman was admitted to the hospital with anorexia, weakness, and persistent coughing. The imaging exams revealed a solid, promiscuous lesion of 16 × 14 cm in dimensions located into the small pelvis, surrounding the uterus and the ovaries. The patient underwent exploratory laparotomy. The mass was removed and the histological examination of the specimen revealed an advanced mesodermal adenocarcinoma of the ovary (MMMT). Nine days after the operation the patient presented with metastatic lesions in the mouth as well as the lungs. Within a month after the discharge from the hospital metastatic lesions of the MMMT were also depicted in the CT brain scan. Conclusion. Despite the fact that sarcomas have a long-term metastatic potential, to our knowledge this is the first case of Müllerian adenosarcoma presenting with such extraperitoneal metastases.